2015
DOI: 10.1186/s13045-014-0098-9
|View full text |Cite
|
Sign up to set email alerts
|

Non-myeloablative allogeneic hematopoietic cell transplantation following fludarabine plus 2 Gy TBI or ATG plus 8 Gy TLI: a phase II randomized study from the Belgian Hematological Society

Abstract: BackgroundFew studies thus far have compared head-to-head different non-myelooablative conditioning regimens for allogeneic hematopoietic cell transplantation (allo-HCT).MethodsHere, we report the results of a phase II multicenter randomized study comparing non-myeloablative allo-HCT from HLA-identical siblings (n = 54) or from 10/10 HLA-matched unrelated donors (n = 40) with either fludarabine plus 2 Gy total body irradiation (Flu-TBI arm; n = 49) or 8 Gy TLI + anti-thymocyte globulin (TLI-ATG arm; n = 45) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 30 publications
0
32
3
Order By: Relevance
“…Indeed, following both HLAhaploidentical and HLA-matched HCT, faster immune reconstitution has been associated with lower relapse rates and better survival (7,48), while favoring Treg homeostasis improved steroid-refractory chronic GVHD (41). In the current study, we compared immune recovery in a cohort of 53 patients included in a prospective multicenter randomized study comparing two widely used nonmyeloablative conditioning regimens (25). The main findings of the current analyses are discussed below.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, following both HLAhaploidentical and HLA-matched HCT, faster immune reconstitution has been associated with lower relapse rates and better survival (7,48), while favoring Treg homeostasis improved steroid-refractory chronic GVHD (41). In the current study, we compared immune recovery in a cohort of 53 patients included in a prospective multicenter randomized study comparing two widely used nonmyeloablative conditioning regimens (25). The main findings of the current analyses are discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…The study was registered in clinicaltrial.gov (NCT00603954). The clinical results of the study (including the data from the 94 patients) have been reported elsewhere (25).…”
Section: Study Populationmentioning
confidence: 99%
“…30 A previous multicenter randomized phase II study from Belgium comparing TLI-ATG to low-dose TBI-fludarabine in patients with HLA-matched donors showed similar outcomes with higher rates of NRM and GVHD in the TBI-fludarabine arm, higher rates of relapse in the TLI-ATG arm, and equivalent OS at 4 years. 31 Our data also compare favorably to other RIC regimens incorporating posttransplant cyclophosphamide (PT CY) or bortezomib for GVHD prophylaxis. Gaballa et al 32 used PT CY in combination with a RIC regimen of fludarabine, melphalan, and thiotepa in the setting of 9 of 10 MMUD HCT and haploidentical HCT and reported NRM rates at 1 year of 31% and 21%, respectively; acute GVHD grade II-IV at day 1100 rates of 33% and 28%, respectively, and grade III-IV rates of 13% and 3%, respectively; chronic GVHD rates at 2 years of 19% and 24%, respectively; and relapse rates at 1 year of 25% and 19%, respectively.…”
Section: Discussionmentioning
confidence: 73%
“…Male donor, male recipient 23 (32) 70 (36) Male donor, female recipient 14 (19) 50 (26) Female donor, male recipient 22 (31) 41 (21) Female donor, female recipient 13 (18) 32 (17) CMV serologic status Donor and/or recipient seropositive 54 (75) 130 (67) Donor and recipient seronegative 18 (25) 63 (33) Data are presented as n (%) unless otherwise indicated. *Other B-cell non-Hodgkin lymphoma includes 1 patient with nodal marginal zone lymphoma and 1 patient with lymphoplasmacytic lymphoma.…”
Section: Sex Mismatchmentioning
confidence: 99%
See 1 more Smart Citation